2014
DOI: 10.1016/j.sbspro.2014.12.418
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Parenting Styles, Emotion Recognition and Regulation in Relation to Psychological Well-being

Abstract: The purpose of the current study was to examine the link among perceived parenting styles, emotion recognition, emotion regulation, and psychological well-being in terms of obsessive-compulsive disorder and social anxiety symptoms. For the purpose of this study, 522 adults between the ages of 18 and 36 participated in the current study. Multiple regression analyses with split-sample validation method revealed that maternal rejection, emotion recognition, cognitive reappraisal and suppression were associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 25 publications
0
13
0
2
Order By: Relevance
“…Gross and Levenson (1997) made a research on the effect of emotion regulation on mental health and they reported that there was a decrease in happiness and meaningful behaviors of the group that suppressed emotions. In Aka's (2011) research, he showed the relations of different parent attitudes, emotion regulation styles and processes of depression, obsessive compulsive disorder and social anxiety symptoms. In this research, it was determined that suppression, which is one of the emotion regulation strategies of university students, varies according to mother profession and educational background.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gross and Levenson (1997) made a research on the effect of emotion regulation on mental health and they reported that there was a decrease in happiness and meaningful behaviors of the group that suppressed emotions. In Aka's (2011) research, he showed the relations of different parent attitudes, emotion regulation styles and processes of depression, obsessive compulsive disorder and social anxiety symptoms. In this research, it was determined that suppression, which is one of the emotion regulation strategies of university students, varies according to mother profession and educational background.…”
Section: Discussionmentioning
confidence: 99%
“…In the research by Kümbül-Güler and Emeç (2006), they determined that optimism and life satisfaction are related to one another. The research of Aka (2011) showed the relations of different parent attitudes, emotion regulation styles and processes of depression, obsessive compulsive disorder and social anxiety symptoms. In the research of Özbay, Palancı, Kandemir and Çakır (2012), regulating emotions (cognitive restructuring) was the most significant variable in the research model that predicted subjective wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that perceived parenting styles play an important role in regulating emotions and development of emotion regulation in children and adolescents ( 41 , 42 ). In addition, happiness is another factor that is positively related to perceived parenting styles ( 43 ).…”
mentioning
confidence: 99%
“…In general, colleges and the society must provide the ATYIs with good learning and social environments, so that they could keep a healthy mental state. More importantly, the ATYIs must be lifted out of the plight of low income (Aka and Gencoz, 2014). Considering the gender difference in mental health, more attention should be paid to females.…”
Section: Practical Significancementioning
confidence: 99%